(untitled) (Journal of Pharmaceutical Negative Results, 2022)
In India, liver cirrhosis ranks as the tenth leading cause of death. Sickness absenteeism and lost man-days are significantly influenced by the cost of treatment. The purpose of this study was to evaluate Terlipressin's effectiveness with albumin to albumin's effectiveness when used alone in hepatorenal syndrome patients. There were two groups each with 80 patients. Albumin was given to Group 1, Terlipressin and albumin to Group 2. The social sciences-specific statistical programme IBM SPSS version 20 was used for all data analysis. We used cross-tabulation and frequency distribution to construct the tables. We display our data's mean, SD, and median (minimum–maximum). To compare continuous variables, the Student's t test and the Mann-Whitney U test were applied. We used Fisher's exact test and Pearson Chi-square to assess categorical variables. The cutoff for statistical significance was p 0.05. study comparing MELDs (Model for end stage liver disease). The MELD ratings did not vary between treatment groups, as indicated by the p value of 0.435. Terlipressin and albumin treatment resulted in a complete response in 60% of patients while having no effect in the other 40%. 85% of patients did not get better on albumin alone, and only 15% of them totally recovered. Having a p value of 0.000032, statistically significant. More patients in the group that got both terlipressin and albumin had complete responses to therapy. When given together, terlipressin and albumin may be more effective at treating hepatorenal syndrome.